Seamless phase II/III trials - Garrett-Mayer, Elizabeth; O’Connell, Nathaniel (Henry Stewart Talks, 2016)
Background and settings appropriate for implementing seamless trial designs, Benefits and potential drawbacks of seamless designs, Real world examples of seamless trial designs in completed trials